Assessing statistical significance in microarray experiments using the distance between microarrays. - Douglas Hayden; Peter Lazar; David Schoenfeld; Inflammation and the Host Response to Injury Investigators (PLoS ONE, 2009)
We propose permutation tests based on the pairwise distances between microarrays to compare location, variability, or equivalence of gene expression between two populations. For these tests the entire microarray or some pre-specified subset of genes is the unit of analysis. The pairwise distances only have to be computed once so the procedure is not computationally intensive despite the high dimensionality of the data. An R software package, permtest, implementing the method is freely available from the Comprehensive R Archive Network at http://cran.r-project.org.